Effect of Respiratory Muscle Training Combined with Electromyographic Biofeedback Training on Swallowing Function and Aspiration Pneumonia after Stroke - Ye TIAN; Kehui HU; Huan YANG; Ruige LIANG; Wei WANG; Cui LIU; Yi ZHANG (康复学报)
Objective:To study the effect of respiratory muscle training combined with electromyographic biofeedback training on swallowing function and aspiration pneumonia after stroke.Methods:Sixty stroke patients with dysphagia were randomly divided into three groups, 20 cases in each group: the group A treated with swallowing function training, the group B treated with electromyographic biofeedback training and swallowing function training, and the group C treated with respiratory muscle training, electromyographic biofeedback training, and swallowing function training. Before and after treatment, the integrated electromyography (iEMG) of suprahyoid muscles and Wawada drinking water experiment were used to evaluate the swallowing function and therapeutic effect. The incidence of aspiration pneumonia in three groups was analyzed by the diagnostic criteria of aspiration pneumonia.Results:The iEMG of suprahyoid muscles of patients in three groups were better than pretreatment (P<0.05), while the group C was statistically significant than the other groups (P<0.05). The incidence of aspiration pneumonia in the group A, B and C was 35.00%, 15.00%, 5.00%respectively, and the difference in three groups was statistically significant (P<0.05). The effective rate of three groups was statistically significant difference (P<0.05).Conclusion:Respiratory muscle training and electromyographic biofeedback training is effective to improve the swallowing function and reduce the incidence of aspiration pneumonia of stroke patients with dysphagia.